At the root of the North-South cooperation gap in Italy: Preferences or beliefs? - Maria Bigoni; Stefania Bortolotti; Marco Casari; Diego Gambetta (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2017)
The marked difference in the development of the North and the South of Italy represents a prototypical case of seemingly intractable within-country disparities. Recent research found that a plausible determinant of this socio-economic gap would be a difference in the ability to cooperate. Through a laboratory experiment we investigate whence this difference derives, whether from different preferences or from different beliefs. Our findings indicate that Northerners and Southerners share the same individual pro-social preferences, and that the cooperation gap lies rather in the pessimistic beliefs that Southerners have about their cooperativeness. Southerners, furthermore, manifest a stronger aversion to social risk, as compared to the risk of nature. A policy implication is that an intervention or an event that reduced pessimistic beliefs would directly boost cooperation levels.
Keywords: C72; C93; Z13; 330